Penerapan Smart Court System Untuk Mewujudkan Peradilan Agama Yang Modern dan Akseleratif - wafie, Slamet Ahmad (LPPM UNU BLITAR, 2024)
Religious courts in Indonesia are still facing various challenges and problems. One of them is the manual trial process that takes a long time, limited information, and lack of transportation. This can hamper the effectiveness and efficiency of the administration of religious courts in resolving cases. Smart court system is an innovative solution to overcome these challenges. Smart court system is an information technology-based system that provides various religious court services. The purpose of this research is to help speed up the trial process, and improve access to information. This research uses the method of descriptive analytical and also uses normative empirical research. Where normative research is legal research that places the law as a building system of norms. Basically, normative research uses the rules in the applicable legal provisions such as articles in the legislation.. The result of this research shows that the implementation of Smart Court System is a step forward in realising a modern and accelerative religious court. Smart court system can help increase the effectiveness and efficiency of religious courts in resolving cases, so as to provide faster and more precise justice to the community.Keywords: smart court system, religious court, effectiveness